Light Microscopy vs PCR Performance in Detecting Plasmodium knowlesi: Indonesia 2011−2020 - Nisa Fauziah; Muhammad Yusuf Zakiyyudin; Savira Ekawardhani; Naufal Fakhri Nugraha; Jontari Hutagalung (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
The emergence of life-threatening zoonotic Plasmodium knowlesi infection poses a growing challenge for Indonesia and other Southeast Asian countries. Accurate and timely diagnosis is critical; however, Plasmodium knowlesi is challenging to identify using light microscopy—the current gold standard for malaria diagnosis—potentially hindering surveillance and case management. This study aims to compare the performance of light microscopy and PCR in detecting Plasmodium knowlesi malaria by analyzing national malaria surveillance data collected between 2011 and 2020. This study was a retrospective analysis. Samples included thick blood films, thin blood films, and dried blood spots, which were referred to the National Laboratory of Parasitology Referral of Indonesia. All samples were examined using light microscopy and confirmed using polymerase chain reaction (PCR), the reference standard for assessing diagnostic accuracy. Compared to PCR, light microscopy demonstrated an excellent sensitivity of 100% (95% CI=92.7–100) and a negative predictive value of 100% (95% CI=78.2–100). However, its specificity was low at 55.6% (95% CI=35.3–74.5), with a positive predictive value of 80.3% (95% CI=72.8–86.2), indicating a frequent misidentification of Plasmodium knowlesi as other Plasmodium species. In conclusion, while light microscopy is highly sensitive and valuable for initial screening, its poor specificity limits its role in definitive diagnosis of Plasmodium knowlesi malaria. PCR remains essential for accurate identification and confirmation, particularly in regions where zoonotic malaria is prevalent.